Trombolisis dengan Panduan Kateter pada Pasien dengan Iskemia Tungkai Akut Derajat IIB - Yanna Indrayana; Djanggan Sargowo (Jurnal Kardiologi Indonesia, 2015)
Acute limb ischemia was defined as sudden decrease in limb perfusion of less than 14 days duration, resulting in variable ischaemic clinical manifestation and potential risk of limb loss. We reported a case female 64 years old with sudden onset of right leg pain in last 3 days with history of hipertension, Diabetes Mellitus and heart failure. From physical examination of lower extremity was found pulselessness, pallor, paresthesi, poikilothermia, paralysis, and pain at the level of A. Poplitea dextra. Diagnosis was confirmed with Duplex Ultrasonography. From arteriography we found thrombus with subtotal occlusion at proximal a. Femoralis dextra and diffuse stenosis at the distal. Operation was not carried out as the request of the patient and it was decided to performed Catheter-directed Thrombolysis. In evaluation there was flow improvement at a. Femoralis dextra but it did not reach peripheral perfussion due to reperfussion injury.